2016
DOI: 10.3174/ajnr.a4704
|View full text |Cite
|
Sign up to set email alerts
|

Inflow Jet Patterns of Unruptured Cerebral Aneurysms Based on the Flow Velocity in the Parent Artery: Evaluation Using 4D Flow MRI

Abstract: BACKGROUND AND PURPOSE:Inflow jet characteristics may be related to aneurysmal bleb formation and rupture. We investigated the visualization threshold on the basis of the flow velocity in the parent artery to classify the inflow jet patterns observed on 4D flow MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The results of our study concur with Futami et al's 18 and Khan et al's studies, 11 which demonstrated that local WSS had a significant association with AWE, as shown in figures 4A and 5A,B. These studies reported that when the aneurysm wall was exposed to low WSS, the vascular permeability may be increased, which manifested as AWE.…”
Section: Association Between Wss and Awesupporting
confidence: 92%
See 2 more Smart Citations
“…The results of our study concur with Futami et al's 18 and Khan et al's studies, 11 which demonstrated that local WSS had a significant association with AWE, as shown in figures 4A and 5A,B. These studies reported that when the aneurysm wall was exposed to low WSS, the vascular permeability may be increased, which manifested as AWE.…”
Section: Association Between Wss and Awesupporting
confidence: 92%
“…The inflow jet pattern was defined as concentrated (figure 3A), diffuse (figure 3B) and unvisualised 18 -concentrated inflow jet: a bundle of inflow streamlines intruding into the aneurysm dome with a dispersion of <20% of the width of the streamline bundle at the aneurysm orifice; diffuse inflow jet: inflow streamlines intruding into the aneurysm dome with a dispersion of >20% of the width of the streamline bundle at the aneurysm orifice and unvisualized inflow jet: no inflow streamlines into the aneurysm. 18 Vorticity=abs (ζx, ζy, ζz) (with ζx=δw/δy−δv/δz, ζy=δu/ δz−δw/δx, ζz = δv/δx−δu/δy), where u, v and w are the vector components of the velocity in the segmented 3D space and x, y and z are the directions in the Cartesian k-space. 23 The segmentation of the IA (figure 3C) and the vorticity calculations (figure 3D) were performed using a custombuilt software programmed in MATLAB and Python.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research groups have reported flow conditions at the aneurysm neck with an in vivo hemodynamic assessment by using a 1.5T MR scanner and with an emphasis on the measurability and influential factors of neck flow. [12][13][14] Nevertheless, to our knowledge, few reports have investigated the relationship between the ostium and FD treatment response. 15,16 We hypothesized that different FD treatment responses were related to aneurysm features, and our study focused on the aneurysm geometries and hemodynamics at the ostium.…”
mentioning
confidence: 99%
“…[1][2][3][4]7,8 However, CFD analysis is based on assumptions and approximations regarding blood properties, vessel wall compliance, and flow conditions, [1][2][3][4] and the location of the vortex core line depends on mathematic definitions. 8 Although 4D flow MR imaging, based on time-resolved 3D cine phase-contrast MR imaging techniques, has been used to evaluate the hemodynamics in human cerebral aneurysms, [9][10][11][12] the visualization of aneurysm vortex cores with this imaging technique has not been reported. Identification of vortex cores on 4D flow MR imaging may be an alternative to CFD analysis of aneurysm models and may lead to new insights into the role of vortex cores in aneurysm behavior.…”
mentioning
confidence: 99%